Evaluación de los co-beneficios ambientales y económicos del aprovechamiento energético de las excretas porcinas - Ramírez Islas, Martha Elena (Universidad Autónoma Metropolitana, 2021)
This research aimed to quantify and economically value the environmental co-benefits of energy production from swine manure treatment by anaerobic digestion (AD). The study is focused on the environmental co-benefits assessment of anaerobic digestion systems with energy production and biogas flaring in comparison of conventional manure management as reference. Co-benefits are additional effects to the main benefits, they were estimated quantifying environmental effects by life cycle analysis and determining their monetary value by economic valuation methods. Co-benefits were included to cost/benefit analysis determining their effect on the profitability of the systems; for the economic analysis, energy production were considered the main economic benefit. In order to generate greater certainty on the environmental and economic evaluation of the systems, information was obtained from a swine manure with an anaerobic digestion system in operation. A swine medium farm located in the State of Puebla was selected, the farm has an annual average production of 5,000 head of cattle and a manure (faces and urine) production of 2,807 tons per year treated by AD for electricity generation used for self-consumption. Manure has 22.5% of total solids, which 81% are organic matter, they were divided as solid manure and liquid manure in function of their physical state and the technique used to remove them from animal houses. Base on the matter balance, the 59% (sb) of manure is treated by anaerobic digestion and 41% by composting. This farm is an example of Mexican farms at industrial scale which treat their manure by anaerobic digestion. The liquid manure is treated by anaerobic digestion using covered lagoons at industrial scale (> 1000 m3 ) generating biogas, digestate and liquid effluents. The AD system operate with low total solid content of 3.27%, high hydraulic retention time of 162 days, a low organic load at the entrance of 0.16 kg SVT/m3 .day and biogas yield of 1.2 m3 /kg SVT. Electricity of 251,959 kWh was produced annually from biogas supplied 67% of farm energy demand. Digestate and liquid effluents are treated by aerobic methods producing, as subproducts, compost and treated water used to irrigation. The site characterization generated field data for process parameters and matter and energy flows estimation, which were used to simulate alternative systems of manure management for the environmental impact evaluation. Environmental impacts were evaluated by life cycle assessment (LCA) in systems with energy production (partial and total energy production), the standard practices of biogas flaring and conventional management. Energy production systems generated the most significant environmental benefits on climate change, photochemical oxidation, eutrophication, acidification and fossil and abiotic resource depletion, compared to other systems without energy production. The analysis allowed generating important and useful information that contributes to the inventories of LCA of pig manure treatment by anaerobic digestion in Mexico. Problems related to the bad manure management were identified by the sensitivity analysis in the LCA regarding non-intentional emissions during the AD process and its by-products handling. Significant environmental loads are produced for these problems promoting methane emissions into the atmosphere in greater magnitude if conventional practices managed manure. These findings show the importance of a proper operation during the AD process using correct operating procedures and providing technical training to avoid global warming. Environmental effects obtained by LCA were monetized using different economic valuation methods. According the economic valuation analysis, water resources depletion was the impact with the highest economic value of $359 thousands pesos per year compared to others impact categories; eutrophication and fossil resource depletion had annual amounts greater to $200 thousands pesos, meanwhile climate change impacts presented the lowest economic cost of $36 thousands pesos. LCA and economic valuation of environmental effects allowed estimate environmental cobenefits of $350 to $642 thousands pesos per year in the AD systems compared to conventional management as reference. GEI reduction, eutrophication reduction, decreased fossil and water resource depletion and organic fertilizer substitution were the most critical cobenefits. Energy production from pig manure treated by AD requires an initial investment higher than $12 million of pesos; this investment requirement may limit its implementation. It also requires operational and maintenance costs of $550 to $650 thousand pesos per year. According to the economic analysis, equipment’s preventive and corrective maintenance represents 50% of the total O&M costs. Biogas and energy systems produce annual economic benefits of $336 to $618 thousand pesos due to savings for electricity self-consumption mainly; however, they have not economic feasibility in 20 years, even considering financial support by the Mexican Government and Banks. The low profitability was attributed to the low yields during the AD process and the biogas to energy conversion. Economic profitability was changed when environmental co-benefits were included in the cost/benefit analysis; in this case, a process environmentally profitable was obtained with benefits for the environment and the society. Environmental and economic importance of environmental co-benefits of the energy production from pig manure treatment by anaerobic digestion, measured by LCA and monetized by economic valuation methods, were demonstrated in this study. Co-benefits relevance was reflected on the economic-environmental profitability of the systems. These findings provide elements to continue with government funding for anaerobic digestion systems installation in México, but focused on energy production, high efficiency, best-operating practices, and support for technical training. The present study contributes with important and useful information to support the development of public political programs on energy sustainability in the livestock sector; the management and valorization of livestock wastes; and the implementation of climate change mitigation strategies in the agriculture, forestry and other land use sector (AFOLU). ; La presente investigación tiene como objetivo cuantificar y valorar económicamente los cobeneficios ambientales del aprovechamiento energético del biogás producido por digestión anaerobia de las excretas de cerdo. El estudio se enfoca en la evaluación de los co-beneficios ambientales de sistemas de digestión anaerobia con producción energía y quema de biogás con relación al manejo convencional de las excretas como referencia. La estimación de los co-beneficios o efectos adicionales a los beneficios principales se realizó mediante la cuantificación de los efectos ambientales aplicando análisis de ciclo de vida (ACV) y la determinación de su valor monetario por métodos de valoración económica. Los cobeneficios estimados fueron incorporados al análisis costo/beneficio para determinar su efecto en la rentabilidad de los sistemas; para el análisis económico se consideró la producción de energía eléctrica como principal beneficio económico. Para generar mayor certidumbre en la evaluación ambiental y económica de los sistemas, se obtuvo información de campo de una granja porcícola con un sistema de digestión anaerobia en operación. Se seleccionó una granja porcícola mediana ubicada en el Estado de Puebla con una producción anual promedio de 5,000 cabezas de ganado y una producción de excretas (heces y orina) de 2,807 toneladas al año tratadas en un sistema de digestión anaerobia para la producción de energía eléctrica para autoconsumo. Las excretas producidas tienen un contenido de solidos totales de 22.5%, de los cuales el 81% es materia orgánica, se dividen en excretas sólidas y excretas líquidas en función de su forma física y de la forma en las que son removidas de los criaderos. Con base en el balance de materia, 59% (bs) de las excretas son tratadas por digestión anaerobia y 41% por compostaje. Esta granja ejemplifica la operación de las granjas en el país a escala industrial que tratan sus excretas mediante digestión anaerobia. El tratamiento de las excretas líquidas se realiza en un sistema de digestión anaerobia con digestores tipo laguna anaerobia cubierta a escala industrial (> 1000 m3 ), generando biogás, digestato y efluentes líquidos. El sistema de digestión anaerobia opera con bajos contenidos de sólidos totales de 3.27%, altos tiempos de retención hidráulica de 162 días, una baja carga orgánica de 0.16 kg SVT/m3 /día y un rendimiento de producción de biogás de 1.2 m3 /kg SVT. El biogás es aprovechado para genera 251,959 kWh al año para abastecer el 67% del consumo interno de la granja. El digestato y efluentes líquidos son tratados por métodos aerobios para producir composta y agua para riego como subproductos. La caracterización del sitio generó datos de campo necesarios para estimar parámetros de proceso y flujos de materia y energía para la evaluación de los efectos ambientales y la simulación de los sistemas a evaluar. Los efectos ambientales fueron cuantificados por ACV en sistemas de producción de biogás y energía (producción parcial y producción total de energía), en la práctica de quema de biogás y el manejo convencional. Los resultados obtenidos mostraron que el aprovechamiento energético de las excretas por digestión anaerobia es una tecnología que tiene mayores beneficios ambientales sobre cambio climático, oxidación fotoquímica, eutrofización, acidificación y el agotamiento de recursos fósiles y abióticos, en comparación con los sistemas sin producción de energía. El análisis permitió generar información importante y útil que contribuye a los inventarios de ACV del tratamiento de excretas de cerdo en sistemas de digestión anaerobia en el país. El análisis de sensibilidad del ACV identificó claramente la problemática relacionada con un mal manejo de las excretas; específicamente sobre las emisiones no intencionales en los biodigestores y durante el manejo de los subproductos, lo que genera importantes cargas ambientales que promueven la emisión de metano al ambiente en mayor magnitud que si las excretas se manejaran bajo las practicas convencionales. Los resultados ponen de relevancia la necesidad de tener un buen control y manejo del proceso, mediante prácticas adecuadas de operación. La valoración económica de los efectos ambientales mostró que el uso de los recursos hídricos fue el efecto ambiental con el valor económico más alto ($359 mil pesos anuales) de todas las categorías evaluadas, seguido de la eutrofización y el agotamiento de los recursos fósiles con valores mayores a los $200 mil pesos al año; en tanto que el efecto sobre cambio climático presentó el valor económico anual más bajo de $36 mil pesos. El ACV y la monetización de los efectos ambientales permitieron demostrar que el aprovechamiento energético de las excretas en comparación con el manejo convencional como referencia, genera co-beneficios ambientales con un valor entre los $350 mil y $642 mil pesos al año por la reducción de gases GEI, la reducción de la eutrofización, la disminución del uso de recursos fósiles e hídricos y la sustitución de fertilizantes inorgánicos. Tratar las excretas para producir energía requiere de una inversión inicial mayor a los $12 millones de pesos, lo que podría limitar su implementación, requiere costos de operación y mantenimiento entre los $550 y $650 mil pesos anuales, de los cuales el mantenimiento preventivo y correctivo de los equipos representa 50% del total. Los sistemas generan beneficios económicos directos entre $336 mil y $618 mil pesos anuales, debido principalmente al ahorro del consumo de energía de la red nacional. El análisis costo/beneficio mostró que los sistemas no presentan rentabilidad económica durante un periodo de 20 años, aun considerando el apoyo económico gubernamental y el financiamiento bancario. La baja rentabilidad de los sistemas se atribuyó a los bajos rendimientos del proceso de digestión anaerobia y de la conversión de biogás a energía. La incorporación de los co-beneficios ambientales al análisis costo/beneficio permitió generar sistemas ambientalmente rentables obteniendo beneficios para el medio ambiente y para la sociedad. Esta investigación muestra la importancia ambiental y económica que tienen los co-beneficios ambientales que genera el aprovechamiento energético del tratamiento de las excretas de cerdo por digestión anaerobia, a través del valor monetario de los efectos ambientales medidos por ACV y reflejado sobre la rentabilidad económico-ambiental de los sistemas. Los resultados son una evidencia importante que contribuyen a seguir incentivando el financiamiento gubernamental para la instalación de los sistemas de digestión anaerobia en el país, pero con un enfoque al aprovechamiento energético, bajo esquemas de mejores prácticas, mayor eficiencia operativa y con un fuerte apoyo a la capacitación técnica. El estudio contribuye a la generación de información importante y útil que permite apoyar la toma de decisión para el desarrollo de política pública relacionada con los programas gubernamentales de sustentabilidad energética en el sector pecuario; la gestión, manejo y valorización de residuos ganaderos; y la implementación de estrategias de mitigación al cambio climático en el sector de agricultura, silvicultura y otros usos del suelo (AFOLU).